Reforming of Regional Fiscal Policy as Basis of Increasing Taxation Potential of Territories - Igonina, Lyudmila Lazarevna; Nabiyev, Ramazan Abdulmuminovich; Alimirzoeva, Madina Gamidulakhovna; Gulmagomedova, Gulzar Akhmedullakhovna; Suleymanov, Magomed Magomedovich (International Journal of Economics and Financial Issues, 2016)
The article is devoted to researching problems related to forming regional fiscal policy focused on increasing the taxation potential of territories. The subject of the research is theoretic and methodological basics of pursuing regional fiscal policy focused on developing the taxation potential of the Russian Federation regions. The object of the research is the Russian taxation system, regional fiscal policy, and foreign and national practices of taxation regulation of regional development. The authors consider in details such aspects of the theme as economic and functional content of regional fiscal policy. They argument the conclusion that efficient regional fiscal policy must contribute to stabilizing production and providing economic growth, equalizing conditions of social and economic, and financial development of regions, ensuring full implementation of principles of the taxation system and taxation federalism in the Russian Federation based on the unified economic and taxation space, establishing and providing financial and economic warranties of the local self-governance, providing all levels of government with monetary means that are sufficient for pursuing economic and social policy as well as fulfilling the imposed functions and performing tasks by relevant governmental authorities. The article stipulates the conclusion that an increase in efficiency of regional fiscal policy has an impact on volumes of tax revenues in budgets of the subjects of the Russian Federation and finally contributes to the development of the taxation potential of territories. It arguments the conclusion that the basic goal of regional fiscal policy is to increase the region’s own taxation potential by increasing the revenue base of regional budgets to carry out expendable obligations to provide economic growth. Key words: regional fiscal policy, taxation federalism, budgets of territories, revenues base, tax authorities. JEL Classifications: H20, H21, H30, H39.